Developing Professionally through Online Activities: Reflections and Revelations - Karki, Sujeet; Neupane, Bharat Prasad (KMC Journal, 2025)
Online professional development has significantly impacted the personal and professional lives of a language teacher during and after the COVID-19 pandemic. In this autoethnographic study, I (the first author) unveil my professional development activities as an English language teacher during and after the pandemic. I have collected the data through my personal lived experiences, narratives, memories and reflections, and I have embraced the interpretations. I subscribe to connectivism and experiential theory and interweaved with my professional development journey. The data were analyzed using the Gibbs (2008) thematic analysis framework. As this article was written based on the online professional development experiences of the first author, the first person pronoun indicated him, and the role of the second author was to conceptualize the article, suggest the first author during the writing process, review, copy edit and finalize the article. The study revealed a significant contribution of professional development activities like global networking, rapport building with educators, creation of digital content through online resources and interactions on social media platforms, and attending MOOC courses, which can enhance teachers’ professional development.